Mazmur dan Teologi Tanah: Kritik Profetis terhadap Mafia Tanah di Indonesia - Dwi Maria Handayani (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
Agrarian issues are a serious structural problem in Indonesia, especially through land-mafia practices involving the seizure of indigenous lands, certificate manipulation, and collusion with those in power. In this context, the Book of Psalms offers a relevant theological reflection for critiquing agrarian injustice. This article analyzes the theme of land in several key passages—Psalm 24:1, 37:11, 65:9–13, 85:12–13, 19:1–4, 104, 79, and 137—using a biblical-theological approach. The study finds that, in the Psalms, land is understood not as a commodity but as God’s gift—one that must be managed justly, entrusted to the vulnerable, and cared for in its fertility. This perspective presents a prophetic critique of land-mafia practices that violate principles of justice, rob marginalized communities of their rights, and damage the environment. By positioning the Psalms as voices of prayer, lament, and hope, the article proposes an active role for the church and public theology in advocating for agrarian justice, asserting that resistance to land-mafia systems is an act of faith to preserve the land as God’s possession and as a shared source of life.